2019
DOI: 10.1080/14767058.2019.1602603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early umbilical cord clamping versus delayed clamping on maternal and neonatal outcomes: a Jordanian study

Abstract: Objective: To compare the effects of early versus delayed cord clamping of term births on maternal and neonatal outcomes. Method: A quasi-experimental study was conducted at the Jordan University Hospital in Amman. One hundred twenty-eight mothers expecting a full-term singleton baby were assigned to delayed cord clamping (90 seconds) or early cord clamping (<30 seconds). Results: Delayed cord clamping was associated with higher hemoglobin levels among newborns after 12 hours. On the other hand, early cord cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The timing of cord clamping was 180 s or longer demonstrating neurodevelopmental benefits in low-risk populations [17,18]. DCC after one minute is a practice that has been shown to be beneficial in spontaneous births [19][20][21]. The infants born by ECS showed a lower value of red blood cells than those birth by VD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of cord clamping was 180 s or longer demonstrating neurodevelopmental benefits in low-risk populations [17,18]. DCC after one minute is a practice that has been shown to be beneficial in spontaneous births [19][20][21]. The infants born by ECS showed a lower value of red blood cells than those birth by VD.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that affect placental transfusion appear to be uterine contractility. CS reduces placental transfusion due to maternal hypotension and insufficient uterine contractions [11][12][13][14][15][16][17][18][19][20][21][22]. Such reduction is even more pronounced by ECS than in emergency CS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed umbilical cord clamping can increase neonatal blood volume and reduce neonatal anaemia and related complications caused by iron deficiency; in addition, it can significantly reduce intraventricular haemorrhage in premature infants and improve some aspects of nervous system development in premature infants with no adverse effects on maternal health (Andersson et al., 2015; Mohammad et al., 2019; Nagano et al., 2018; Rabe, Diaz‐Rossello, Duley, & Dowswell, 2012). According to our review of the literature, studies of the effect of delayed umbilical cord clamping on the suture pain of maternal perineal wounds have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed umbilical cord clamping means that the umbilical cord is clamped 30 to 90 s after delivery or after the umbilical cord pulsation disappears spontaneously (Mohammad, Tailakh, Fram, & Creedy, 2019; Qian, Ying, Wang, Lu, & Hua, 2019); at present, this line of research is also the focus of clinical attention. The umbilical cord is the channel for nutrient metabolism and material exchange between foetus and mother.…”
Section: Introductionmentioning
confidence: 99%
“…Even in high-income countries like the USA, the current literature on the timing of cord clamping is not reflected in the practice [40]. Several studies have revealed the benefits in placental transfusion, increased haematocrit level, cerebral oxygenation and blood pressure, gradual transition to extrauterine, and long-term neurodevelopmental outcomes [5,9,[41][42][43].…”
Section: Perceptions About Umbilical Cord Clampingmentioning
confidence: 99%